The role of next generation sequencing in the differential diagnosis of caroli’s syndrome - Smolović B; Muhović D; Hodžić A; Bergant G; Peterlin B (Balkan Journal of Medical Genetics, 2018)
We report the case of a 41-year-old man on conservative treatment for more than 20 years for chronic renal insufficiency, chronic hepatitis and recurrent cholangitis. Following lengthy and extensive diagnostics, the differential diagnosis included primary sclerosing cholangitis and Caroli’s disease (CD). To solve the diagnostic challenge, next generation sequencing (NGS) was performed to distinguish between the disorders possibly present in the patient. The diagnosis of CD became evident after two rare known pathogenic mutations were detected in the poly-ductin 1 (PKHD1) gene, c.370C>T (p.Arg124Ter) and c.4870C>T (p.Arg1624Trp). In this case, NGS was instrumental in solving the diagnostic challenge, allowing differentiation among the proposed genetic and non-genetic ethiologies.